FROM HADITH TO HEALTH: Contextualizing the One-Third Eating Principle in Light of Modern Nutritional Science - Hildayana, Tri; Darta, Ali (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
This study investigates the integration of Hadith teachings on dietary practices with modern nutritional science within the Muslim community of Tanjung Morawa B Village. Employing an ethnographic approach, the research draws on in-depth interviews with 40 respondents and participatory observations of 20 individuals. The findings reveal that 77.5% of participants practice the